2017
DOI: 10.3390/molecules22091473
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Based Products Tested on Pathogens Isolated from Mastitis Milk

Abstract: Bovine mastitis a major disease that is commonly associated with bacterial infection. The common treatment is with antibiotics administered intramammary into infected quarters of the udder. The excessive use of antibiotics leads to multidrug resistance and associated risks for human health. In this context, the search for alternative drugs based on plants has become a priority in livestock medicine. These products have a low manufacturing cost and no reports of antimicrobial resistance to these have been docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 53 publications
2
39
0
1
Order By: Relevance
“…Geleneksel kullanımları, fitokimyasal bileşimleri ve farmakolojik etkileri nedeniyle bitkiler uzun zamandır dikkatleri üzerine çekmektedir. 1 Literatürde bitkilerin tedavi edici etkilerini gösteren çok sayıda çalışma olup; 20.000'den fazla tıbbi bitkinin zatürre, diyare, ülser, soğuk algınlığı, bronşit ve solunum yolu hastalıkları gibi çeşitli hastalıkların tedavisinde kullanıldığı Dünya Sağlık Örgütü tarafından bildirilmiştir. 2 Kendilerine karşı kullanılan antimikrobiyal ilaçlara karşı mikroorganizmaların direnç geliştirme potansiyelleri bulunmaktadır.…”
Section: Introductionunclassified
“…Geleneksel kullanımları, fitokimyasal bileşimleri ve farmakolojik etkileri nedeniyle bitkiler uzun zamandır dikkatleri üzerine çekmektedir. 1 Literatürde bitkilerin tedavi edici etkilerini gösteren çok sayıda çalışma olup; 20.000'den fazla tıbbi bitkinin zatürre, diyare, ülser, soğuk algınlığı, bronşit ve solunum yolu hastalıkları gibi çeşitli hastalıkların tedavisinde kullanıldığı Dünya Sağlık Örgütü tarafından bildirilmiştir. 2 Kendilerine karşı kullanılan antimikrobiyal ilaçlara karşı mikroorganizmaların direnç geliştirme potansiyelleri bulunmaktadır.…”
Section: Introductionunclassified
“…Whole plants or parts thereof are used to prepare different medications (Balakrishnan et al, 2017;Rastogi et al, 2015). Studies confirm that plants and plant-based medications have an inhibitory and antimicrobial effect on MC agents (Pașca et al, 2017). Therefore, the use of medicinal plants implies a promising perspective for the treatment of MC.…”
Section: Introductionmentioning
confidence: 99%
“…Hashemzadeh-Cigari et al (2014) have showed improved feed intake, performance, udder health, ruminal fermentation, and plasma metabolites in cows with moderate or high SCC in the milk due to their diet supplementation with a phytobiotics-rich herbal mixture. In turn, an experiment performed by Pasca et al (2017) to test the inhibitory effect of phytobiotics obtained from several plant species has shown a stronger antimicrobial activity of the coupled use of the phytobiotics compared to the individual application of each plant-based products. In the literature available, not many researchers deal with the influence of garlic on mastitis prevention, especially at organic farms.…”
Section: Introductionmentioning
confidence: 99%